Efek Pemberian Metformin dan Metformin+Glimepiride terhadap Kadar HbA1c pada Pasien Diabetes Mellitus Tipe 2 - Fitri Apriliany; Elis Cholisah; Karina Erlianti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Diabetes is a chronic metabolic disease and management of DM begins with a helthy lifestyle with early administration of antidiabetic drug. Metformin is the first line therapy in the management of DM. Combination therapy is given if blood sugar level and HbA1c level cannot be controlled with single therapy. This study aimed to determine the effect of giving metformin and metformin+glimepiride on HbA1c levels in DM2 patients. The inclusion criteria were patients DM, received oral antidiabetic at least 6 months, completed medical record, and can speak Indonesia. Exclusion criteria included DM patients receiving insulin therapy, TB patients, patients with mental disorders, and pregnant/breastfeeding women. Sociodemographic data, description of prescribing patterns, and achievement of HbA1c levels were described descriptively. Data analysis using the Wilcoxon test. Respondents in this study were 69 patients,  dominated by women (71%). The types of therapy used were metformin (59.4%) and metformin+glimepiride (40.6%). Achievement of metformin + glimepiride HbA1c levels (67.9%), metformin (48.8%). The difference in decreasing HbA1c levels with metformin (-0.31%±0.38 mg/dL) and metformin+glimepiride -0.33%±0.54 mg/dL (p = 0.000). The results of the analysis showed that there is a significant effect of metformin alone on decreasing HbA1c levels and the addition of glimepiride (metformin + glimepiride) on reducing HbA1c levels in diabetes cannot be controlled with metformin. The implication of this study is as input for comprehensive management guidelines that can be used in an effort to reduce the prevalence of DM. Good management is needed to achieve therapeutic outcomes.